Cerebellar volume in schizophrenia and bipolar I disorder with and without psychotic features. (28th November 2014) - Laidi, C.; d'Albis, M.‐A.; Wessa, M.; Linke, J.; Phillips, M. L.; Delavest, M.; Bellivier, F.; Versace, A.; Almeida, J.; Sarrazin, S.; Poupon, C.; Le Dudal, K.; et al.
<x xml:space="preserve">Abstract</x> Objective There is growing evidence that cerebellum plays a crucial role in cognition and emotional regulation. Cerebellum is likely to be involved in the physiopathology of both bipolar disorder and schizophrenia. The objective of our study was to compare cerebellar size between patients with bipolar disorder, patients with schizophrenia, and healthy controls in a multicenter sample. In addition, we studied the influence of psychotic features on cerebellar size in patients with bipolar disorder. Method One hundred and fifteen patients with bipolar I disorder, 32 patients with schizophrenia, and 52 healthy controls underwent 3 Tesla MRI. Automated segmentation of cerebellum was performed using FreeSurfer software. Volumes of cerebellar cortex and white matter were extracted. Analyses of covariance were conducted, and age, sex, and intracranial volume were considered as covariates. Results Bilateral cerebellar cortical volumes were smaller in patients with schizophrenia compared with patients with bipolar I disorder and healthy controls. We found no significant difference of cerebellar volume between bipolar patients with and without psychotic features. No change was evidenced in white matter. Conclusion Our results suggest that reduction in cerebellar cortical volume is specific to schizophrenia. Cerebellar dysfunction in bipolar disorder, if present, appears to be more subtle than a reduction in cerebellar volume.